2011
DOI: 10.1007/s10450-011-9346-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the energetic topography of bivariate heterogeneous surfaces from adsorption isotherms

Abstract: The reversible adsorption process occurring on patchwise heterogeneous bivariate surfaces is studied by Monte Carlo simulation and mean-field approximation. These surfaces are characterized by a collection of deep and shallow adsorbing patches with a typical length scale l. Patches can be either arranged in a deterministic chessboard structure or in a random way. Previous studies showed that the topography of a given surface can be obtained from the knowledge of the corresponding adsorption isotherm and a refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The density functional theory yields similar results [26], while the quasi-chemical approximation yields a more complex isotherm equation [14]. For heterogeneous surfaces an average of Langmuir isotherms was obtained [17,18]. An intriguing case that is still not well understood is the region of subcritical temperatures where first-order phase transitions can occur.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The density functional theory yields similar results [26], while the quasi-chemical approximation yields a more complex isotherm equation [14]. For heterogeneous surfaces an average of Langmuir isotherms was obtained [17,18]. An intriguing case that is still not well understood is the region of subcritical temperatures where first-order phase transitions can occur.…”
Section: Introductionmentioning
confidence: 96%
“…where µ is the chemical potential and λ j = 0, 1 is the site occupancy. Nevertheless, heterogeneous surfaces have also been investigated [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, simple heterogeneous surfaces, characterized by two kinds of nonequivalent sites, have also been intensively used in modeling adsorption [29][30][31][32][33] and surface diffusion phenomena [34][35][36][37][38][39][40][41][42][43][44]. In the first case, adsorption on bivariate surfaces with square patches and strip topographies has been studied through Monte Carlo simulations for adparticles with nearest-neighbor interaction energy, at a fixed temperature [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the study was extended to include the effects of temperature on the adsorption process [31]. It was found that both the adsorption isotherms and the differential heat of adsorption follow scaling laws involving the patch size l with a universal exponent, and that this characteristic length defining the topography could, in principle, be obtained from the analysis of experimental results [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…where now θ (T ,μ) not only depends on the adsorptive energy at a given point on the surface but also on the adsorptive energy at (in general)"m" neighboring points, and f (ε 1 ,...ε m ) is a multivariate probability distribution which specifies how adsorptive energies are spatially distributed, or in other words, the energetic topography of the surface. In this context, Bulnes et al [30,31] analyzed the case of bivariate surfaces, with particles interacting through a repulsive interaction by Monte Carlo (MC) simulations. Despite the complexity of the surface, different quantities were identified which scale obeying power laws as a function of the patch length and the difference of adsorptive energy between strong and weak adsorption sites.…”
Section: Introductionmentioning
confidence: 99%